Risk stratification in patients with pulmonary hypertension undergoing transcatheter aortic valve replacement. Issue 20 (11th August 2015) - Lindman, Brian R; Zajarias, Alan; Maniar, Hersh S; Miller, D Craig; Suri, Rakesh M; Arnold, Suzanne V; Webb, John; Svensson, Lars G; Kodali, Susheel; Xu, Ke; Ayele, Girma M; Lin, Fay; et al.
Abstract : Objective: Pulmonary hypertension (PH) is associated with increased mortality after surgical or transcatheter aortic valve replacement (TAVR) for aortic stenosis (AS), and when the pulmonary artery pressure is particularly elevated, there may be questions about the clinical benefit of TAVR. We aimed to identify clinical and haemodynamic factors associated with increased mortality after TAVR among those with moderate/severe PH. Methods: Among patients with symptomatic AS at high or prohibitive surgical risk receiving TAVR in the Placement of Aortic Transcatheter Valves (PARTNER) I randomised trial or registry, 2180 patients with an invasive measurement of mean pulmonary artery pressure (mPAP) recorded were included, and moderate/severe PH was defined as an mPAP ≥35 mm Hg. Results: Increasing severity of PH was associated with progressively worse 1-year all-cause mortality: none (n=785, 18.6%), mild (n=838, 22.7%) and moderate/severe (n=557, 25.0%) (p=0.01). The increased hazard of mortality associated with moderate/severe PH was observed in females, but not males (interaction p=0.03). In adjusted analyses, females with moderate/severe PH had an increased hazard of death at 1 year compared with females without PH (adjusted HR 2.14, 95% CI 1.44 to 3.18), whereas those with mild PH did not. Among males, there was no increased hazard of death associated with any severity of PH. In a multivariable Cox model of patients with moderate/severe PH, oxygen-dependent lung disease, inability to perform a 6 min walk, impaired renal function and lower aortic valve mean gradient were independently associated with increased 1-year mortality (p<0.05 for all), whereas several haemodynamic indices were not. A risk score, including these factors, was able to identify patients with a 15% vs 59% 1-year mortality. Conclusions: The relationship between moderate/severe PH and increased mortality after TAVR is altered by sex, and clinical factors appear to be more influential in stratifying risk than haemodynamic indices. These findings may have implications for the evaluation of and treatment decisions for patients referred for TAVR with significant PH. Trial registration: NCT00530894.